O turismo como fator de descaracterização territorial e sociocultural: a experiência de Itapagipe - Alfaya, Taiz Vieira (2007)
This essay had as objetive to analyse the territorial and social cultural process modifications imposed by the public interventions in the area of Ponta do Humaitá, Itapagipe Peninsula, in order to implement the Via Náutica Project. In the beginning is presented a panorama about the globalization, culture and the sustentability. The examination of these concepts allowed the finding of possible causes for the aggressive way that the public interventions were made in Ponta de Humaitá with the objective of stimulating tourism through big projects, in order to achieve economic development. In this essay we deal with the concepts of growth and economic development with the objective of showing that there is no development without the effective inclusion of the society, and, for this, it is important to take into account the local population identity. The territorial and social cultural patrimony are public welfare, however some places like Ponta de Humaitá have a community of inhabitants that uses the area to socialize, share memories and develop economic activities; that is why, although it is a public space, it is not proper to modify or interfere in the fisical and social cultural quotidian of a society with non-accomplished promises of better conditions and local development through tourism to this region. The sense of belonging, property, identity and the effective boundings with the place need to be considered when planning any action that might offend any of this aspects. The territorial, patrimonial, social cultural and coletive memory preservation should be an obrigatory prerrogative for any intervention, in a place that have an community that is part of these environment, space and these place.